428 Uterine smooth muscle tumors of uncertain malignant potential (STUMP): ultrasound charateristics. (18th September 2019) - Zola, P; Cotrino, I; Baima Poma, C; Viora, E; Ribotta, M; Borella, F; Macchi, C; Potenza, E; Laudani, ME
Abstract : Objectives: Uterine smooth muscle tumors of uncertain malignant potential (STUMP) represent a group of rare and challenging myometrial neoplasms. STUMPs that are followed by a recurrence are biologically low-grade leiomyosarcomas, but using current methods of analysis, this diagnosis cannot be made with certainty until a recurrence has developed. Our objective is to describe ultrasound findings in women with STUMP. Methods: We retrospectively evaluated preoperative sonographic data of patients with histopathological STUMP diagnosis between 2014 and 2018 in Turin S. Anna Hospital, a tertiary center. The tumors were characterized on the basis of ultrasound images and ultrasound reports using the terms and definitions of the Morphological Uterus Sonographic Assesment (MUSA) group. Results: Thirteen patients with STUMP (19 lesions, of which 17 pure STUMP and 2 STUMP with LMS associated) were identified. Using the MUSA terms and definitions most STUMP were poorly or moderately vascularized (69%) and almost all had both circumferential and intra-lesional flows (82%). Only three (16%) STUMP showed shadowing. Outline were well-defined in sixteen cases (84%). All STUMP had non-uniform echogenicity. Eleven (58%) STUMP were isoechoic, two (11%) hyperechoic and six (31%) had mixed echogenicity. Thirteen (68%) STUMP had microcystic anechoic areas. Over 30% of patients had multiple stumps and almost 80% associated myomas. Conclusions: The suspicion of STUMP is supported by the ultrasound finding of a single or multiple lesion, isoechoic or with mixed echogenicity, without shadowing, with regular borders, internal microcystic anechoic areas and vascularization from minimal to high both circumferential and intralesional.